DAMPAK SENGKETA PULAU DOKDO/TAKESHIMA KOREA SELATAN - JEPANG TERHADAP PERKEMBANGAN HALLYU DI JEPANG - Aldean Tegar Gemilang (Global Political Studies Journal, 2019)
This study aims to determine how the impact of the disputed Dokdo Island / Takeshima between South Korea and Japan on the development of Hallyu in Japan Year 2012-2015. The purpose of this study was to determine the impact of the disputed Dokdo / Takeshima between South Korea and Japan on the development of Hallyu in Japan after re-simmering dispute over Dokdo Island / Takeshima by the visit of South Korean President Lee Myung Bak in 2012. Methods The study was qualitative. Most of the data were collected through interviews, literature study, observation, documentation, and online data searches. The study was conducted at the Korean Cultural Center, The Japan Foundation, Library and Documentation Centre of Scientific Information LIPI, and the Embassy of Japan to Indonesia. The results showed that the development of Hallyu in Japan after re-simmering dispute over Dokdo Island / Takeshima between South Korea and Japan in 2012 experiencing barriers. Problems island disputes between countries worsen bilateral relations, in the case of disputed Dokdo / Takeshima also have a negative impact on the cultural development of Hallyu in Japan.